2011
DOI: 10.1038/labinvest.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Additive renoprotective effects of B2-kinin receptor blocker and PPAR-γ agonist in uninephrectomized db/db mice

Abstract: We recently showed that the bradykinin B2 receptor (B2R) blocker icatibant (Icat) and the peroxisome proliferatoractivated receptor-g agonist rosiglitazone (Ros) exerted anti-inflammatory effects in renal tubular cells exposed to a diabetic milieu. This study aims to explore whether these effects can be translated to an experimental model of type 2 diabetic nephropathy (DN). db/db mice and their nondiabetic db/m littermates underwent sham operation or uninephrectomy (Unx) at 10 weeks and received vehicle (Veh)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Unx db/m mice showed a slight increase in systolic blood pressure and serum BUN (P < 0.05) after 8 weeks of treatment; however, Unx did not show any effect on these parameters in db/db mice. As reported in our previous study [31], Unx markedly exaggerated UACR and serum BUN level in db/db mice compared with sham-operated db/db mice in this study. Average UACR of Unx-db/db vehicle group was 2-fold higher than Unx db/db mice receiving BMP7 injection (8612 + − 2037 μg/mg compared with 3549 + − 816.2 μg/mg, P = 0.036).…”
Section: Bmp7 Preserved Kidney Function and Kidney Morphology In Diabsupporting
confidence: 88%
See 1 more Smart Citation
“…Unx db/m mice showed a slight increase in systolic blood pressure and serum BUN (P < 0.05) after 8 weeks of treatment; however, Unx did not show any effect on these parameters in db/db mice. As reported in our previous study [31], Unx markedly exaggerated UACR and serum BUN level in db/db mice compared with sham-operated db/db mice in this study. Average UACR of Unx-db/db vehicle group was 2-fold higher than Unx db/db mice receiving BMP7 injection (8612 + − 2037 μg/mg compared with 3549 + − 816.2 μg/mg, P = 0.036).…”
Section: Bmp7 Preserved Kidney Function and Kidney Morphology In Diabsupporting
confidence: 88%
“…At the age of 9 weeks, mice underwent uninephrectomy (Unx) or sham operation as described previously [31]. Briefly, a dorsalventral incision was made on the right side of the abdominal cavity in anaesthetized mice, the right renal pedicle was identified and ligated followed by carefully dissected out of the kidney.…”
Section: Animal Modelmentioning
confidence: 99%
“…Polymorphisms in the human B 2 R have been linked to increased albuminuria in diabetic patients and to the development of chronic renal failure [28], [29]. In addition, blockade of B 2 R markedly reduced the proteinuria in STZ-diabetic mice and inhibition of B 2 R ameliorated the accelerated nephropathy in uninephrectomized db/db mice, lending support to the pathogenic role of B 2 R in DN [30], [31].…”
Section: Discussionmentioning
confidence: 84%
“…High glucose induced KLK1 and B2R expression in cultured PTEC and in human proximal tubules of the diabetic kidney [9]. Further in vivo data showed that treatment of the diabetic db/db mice with icatibant, a B2R antagonist, partially attenuated proteinuria and histological lesions in renal tissues [16]. In addition, the deletion of B2R protected against the development of streptozotocin (STZ)-induced DN [17].…”
Section: Introductionmentioning
confidence: 98%